Some methods of fish capture in Leyte Gulf and Carigara Bay. - Nombrado, Victorino C. (College of Fisheries, University of the Philippines, 1952)
Most of the fishermen in Leyte and Samar still employ primitive methods of fish capture. The implements they use are the handlines, harpoons with the aid of light and some different forms of fish corals. This is due to the lack of bigger capital needed for the construction and operation of advanced type of gears. Not very many can afford to invest an amount enough to finance the construction of such nets as the bansig, encircling gill net, kabyaw, sapyaw and some other fishing geras that require much capital. However, with the encouraging size and amount of catch being landed by yhe fishermen, more fishermen are induced to construct similar gears. These fishinh geras are operated in the gulf of Leyte, Garigara Bay and Samar seas, which are suitable for both shallow and deep-sea fishing. Here are presented among others the description of the bintol, boling, sapyaw, patuloy, kabayaw and kayagkag all operated in Leyte Gulf and Carigara Bay.